Efektivitas Media Pembelajaran Papan Penjumlahan dalam Meningkatkan Kemampuan Operasi Penjumlahan pada Anak Berkesulitan Belajar - Dinda Laili Sarah Matondang; Martias Z (Ranah Research : Journal of Multidisciplinary Research and Development, 2021)
The research objective was to improve the addition operation ability through the addition board learning media for children with learning difficulties in grade III SD N 11 Pauh Padang. This research uses a quantitative research approach with experimental method and single subject research (SSR) with A1 - B - A2 design. Design A1 - B - A2. At baseline conditions (A1) the child's ability to fluctuate ranges from 5% to 50%. The condition for intervention (B) ranged from 25% to 75%. At the baseline session (A2) it is already in a stable position, namely 100%. The results showed that the effect of the intervention using addition board media was effective in increasing the addition’s operation ability children’s with learning difficulties (X) class III at SD N 11 Pauh Padang.